2004
DOI: 10.1128/jcm.42.7.2902-2906.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Extended-Spectrum Beta-Lactamases Produced by Clinical Isolates of Klebsiella pneumoniae and Escherichia coli from a Korean Nationwide Survey

Abstract: To determine the prevalence and genotypes of extended-spectrum beta-lactamases (ESBLs) among clinical isolates of Klebsiella pneumoniae and Escherichia coli, we performed antibiotic susceptibility testing, pI determination, induction testing, transconjugation, and DNA sequencing analysis. Among the 509 isolates collected from 13 university hospitals in Korea, 39.2% produced ESBLs. ESBL-producing isolates were detected in every region in Korea. A total of 44.6% of the isolates produced both TEM-and SHV-type ESB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
63
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 22 publications
7
63
1
5
Order By: Relevance
“…A surveillance study developed in a University Hospital in Turkey reveals a prevalence of 57.1% Klebsiella pneumoniae ESBL producing strains [23] whereas the general circulation of these strains is of 33-86%. A nationwide survey in Korea aiming to detect the prevalence of ESBL Klebsiella pneumoniae producing strains identified 29% resistance to ceftazidime and 32% to cefotaxime [24]. Our study indicates a large circulation of strains resistant to more than three antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…A surveillance study developed in a University Hospital in Turkey reveals a prevalence of 57.1% Klebsiella pneumoniae ESBL producing strains [23] whereas the general circulation of these strains is of 33-86%. A nationwide survey in Korea aiming to detect the prevalence of ESBL Klebsiella pneumoniae producing strains identified 29% resistance to ceftazidime and 32% to cefotaxime [24]. Our study indicates a large circulation of strains resistant to more than three antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…A ocorrência de mais de um tipo de ESBL em um mesmo isolado é bastante comum, sendo a associação mais frequente a dos tipos TEM e SHV 10 Neste estudo, os métodos fenotípicos constataram que 67,8% dos isolados eram produtores de ESBLs, entretanto, pelo método molecular (PCR) este percentual foi de 93,3%; a comparação entre os métodos revelou pelo Teste para Proporções Populacionais p diferenças significativas (p<0,0001). Por outro lado, empregando-se o teste do qui-quadrado de Independência, demonstrou-se que as ESBLs dos tipos TEM e SHV (detecção molecular) estão associadas aos testes fenotípicos positivos (p<0,05).…”
Section: Discussionunclassified
“…[52]. Whereas studies from China [33] Korea [36] and India [12,53] reported TEM to be more prevalent than SHV.…”
Section: Discussionmentioning
confidence: 91%
“…It was further increased to 77.8% in 2009 [33]. ESBL production of Klebsiella pneumoniae from Thailand ranged from 44.4%-100% [34,35] and Korea 30% [36]. Another Asian Country Iran showed an increase in ESBL production by Klebsiella pneumoniae of 52.5% in 2008 [37] to 59.2% in 2009 [38], reaching 96% by 2010 [39].…”
Section: Discussionmentioning
confidence: 99%